Protecting consumer from unfair terms : a comparative study between Malaysia , United Kingdom and Australia / Azleena Md Khairuddin...[et al.] - Md Khairuddin, Azleena; Azawawi, Nur Aina Syafiqah; Mat, Nur Hidayah; Azman, Sofia (Faculty of Law, 2013)
This research paper is about consumer law in Malaysia , United Kingdom and Australia . This research paper , focuses on the aspect of consumer protection and on the impact of unfair term on consumer in general .For Malaysia this research paper will focus on Consumer Protection act 1999 and Consumer Protection (amendment) act 2010, United Kingdom will focus on Unfair Contract Term Act 1977 and Unfair Term in Consumer Contract Regulation 1999 and for Australia Competition and Consumer Act 2010. This research paper will discuss on the provision related to objective of legislation . Features of legislation which are the definition of consumer, definition of consumer contract, definition of unfair term contract terms conditions in determining unfair contract terms, examples of unfair contract terms ,scope of unfair contract terms law and remedies that can be sought under legislation. Finally, comparison between all three legislation and the most suitable provision and feature will be pick to provide a better protection for consumer in Malaysia.